2020
DOI: 10.1111/jpc.14810
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of neuroblastoma in Australian children: A population‐based study (1983–2015)

Abstract: Background: Neuroblastoma predominantly affects younger children and exhibits heterogeneous behaviour. This study describes incidence and outcomes for neuroblastoma using national population-based data from the Australian Childhood Cancer Registry. Methods:Deidentified data for all children (0-14 years) diagnosed with neuroblastoma and ganglioneuroblastoma from 1983-2015 were extracted. Cause-specific (CSS) and event-free (EFS) survival were estimated using the cohort method. Adjusted hazard ratios (HRs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…als aged 0-12 months, noting a varied range in the age-standardized incidence rate of cases per million: 9.5 in Australia, 10.1 in Southern-Eastern Europe countries, 13.7 in Germany, 13.8 in Italy, and 14.3 in France. [14][15][16][17][18][19] These differences were shown to be driven primarily by variation of incidence rates in the first year of life as well as variation in the human development index (HDI). It is hypothesized that higher HDI results in increased detection of neuroblastoma because of the availability of modern imaging technology and increased access to health care services, 20 the difference found in comparing our comprehensive US data with that of other nations may be in part due to higher HDI in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…als aged 0-12 months, noting a varied range in the age-standardized incidence rate of cases per million: 9.5 in Australia, 10.1 in Southern-Eastern Europe countries, 13.7 in Germany, 13.8 in Italy, and 14.3 in France. [14][15][16][17][18][19] These differences were shown to be driven primarily by variation of incidence rates in the first year of life as well as variation in the human development index (HDI). It is hypothesized that higher HDI results in increased detection of neuroblastoma because of the availability of modern imaging technology and increased access to health care services, 20 the difference found in comparing our comprehensive US data with that of other nations may be in part due to higher HDI in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…In line with prior publications, we found that the overall incidence of neuroblastoma was stable. European data ranging from 1979 to 2016 of over 9000 patients demonstrate increased incidence in individuals aged 0 – 12 months, noting a varied range in the age‐standardized incidence rate of cases per million: 9.5 in Australia, 10.1 in Southern‐Eastern Europe countries, 13.7 in Germany, 13.8 in Italy, and 14.3 in France 14–19 . These differences were shown to be driven primarily by variation of incidence rates in the first year of life as well as variation in the human development index (HDI).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma (NB), a malignant cancer originating from sympathetic nerves, is known to be the most common extracranial solid cancer in childhood, accounting for approximately 15% of all cancer-related paediatric deaths (Matthay et al, 2016;Youlden et al, 2020). Currently, there are multimodal strategies to treat NB, including surgery, radiotherapy, induction chemotherapy, immunotherapy and autologous stem cell transplantation either in combination or separately depending on the clinical features and disease stage (Cañete, 2020;Tas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroblastoma (NB), an aggressive neural crest derived malignancy, is the most common pediatric solid tumor with the majority of cases presenting by 5 years of age, accounting for approximately 15% deaths of total pediatric cancers [1]. NB exerts a wide range of clinical behaviors from spontaneous regressions especially in children less than 1 year to lethal outcome even with intense multimodal therapy due to biologic heterogeneity [2,3].…”
Section: Introductionmentioning
confidence: 99%